Concomitant transmission of dengue, chikungunya and Zika viruses in Brazil: Clinical and epidemiological findings from surveillance for acute febrile illness - Silva, Monaíse Madalena Oliveira (2018)
Brazilian National Council for Scientific and Technological Development [grants 400830/2013-2, and 440891/2016-7 to G.S.R.; and scholarships to I.A.D.P., L.B.T., U.K., M.G.R., and G.S.R.]; the Bahia Foundation for Research Support [PET0026/2013, APP0044/2016, and PET0022/2016 to G.S.R., and scholarship to M.M.O.S.]; the Coordination for the Improvement of Higher Education Personnel, Brazilian Ministry of Education [440891/2016-7 to G.S.R. and scholarship to M.K.]; the National Institutes of Health (USA) [R01 TW009504, R01 AI121207, and U01 AI088752 to A.I.K.], [R24 AI AI120942 to SCW]; the Yale School of Public Health; the Federal University of Bahia; and the Oswaldo Cruz.